Foetomaternal outcome in multifoetal pregnancy in a tertiary rural teaching hospital - Gond, Sneha; Sharma, Partha Pratim; Madhuri, Narra; Barman, Kasturi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Aim of the study was to find out foeto-maternal outcome of multifoetal pregnancy in relation to chorionicity and to analyse the associated risk factors. Methods: This study was a prospective observational study on multifoetal pregnancy conducted at Midnapore medical college and hospital. Statistical analysis was done by chi-square test and statistical significance was set at p-value<0.05. Results: Incidence of multifoetal pregnancy was 1.7%. Modal age group was 20-24 years age and 82% conceived spontaneously. Among chorionicity, Dichorionic diamniotic (DCDA) were 60% followed by 34% Monochorionic diamniotic (MCDA), 4% Monochorionic monoamniotic (MCMA) and 2% Trichorionic triamniotic (TCTA). Among maternal complications preterm labour were present in both twins and triplets followed by anemia. LSCS was required in 60.8 % of twins and common indication was malpresentation. Majority of MC and TC were delivered at gestational age of 31-33 weeks (47.1% MCDA, 50% MCMA and 60% TCTA) and dichorionic delivered at 34-36 week (48.7%). Statistical association between neonatal outcomes and chorionicity were significant in IUGR (p=<0.0001), stillbirth (p=0.0356), congenital anomalies (p=0.0017), discordant growth (p<0.0001), Apgar score <7 (p<0.0001), low birth weight (p=0.014), live birth (p≤0.0001) and NICU admission (p<0.0001). Conclusions: Maternal and perinatal outcome was significant in monochorionic and trichorionic pregnancies compared to dichorionic pregnancies with increased NICU admissions required in monochorionic and trichorionic gestations.